Resiliencia y calidad de vida en familias con un miembro con discapacidad intelectual - Moscoso Quiroz, Angela Valeria (2022)
Raising a child with intellectual disability could be difficult. The responsibilities related to their care, development, education, among other factors, could cause problems in the family functioning. However, despite the pressure and the adverse circumstances to which they are exposed, families could overcome obstacles if they have both internal and external protective factors. Resilience would be one of the most important. The objective of the present study is to review scientific articles related to resilience and quality of life in families with a member with intellectual disability. A systematic review was carried out following the PRISMA guidelines (Urrutia & Bonfill, 2013), using the databases Scopus, EBSCO, Science Direct and Proquest. The analysis focused on studies that evaluated resilience and quality of life in families with a member with intellectual disability. Resilience found to be significantly related with quality of life in families with a member with intellectual disability. Future research should implement longitudinal studies to support the relation between both variables.